Late Miocene provenance change on the eastern margin of the Yinggehai-Song Hong Basin, South China Sea: Evidence from U–Pb dating and Hf isotope analyses of detrital zircons. (March 2015) - Wang, Ce; Liang, Xinquan; Xie, Yuhong; Tong, Chuanxin; Pei, Jianxiang; Zhou, Yun; Jiang, Ying; Fu, Jiangang; Wen, Shunv
Abstract: Understanding the provenance of the reservoir in a sedimentary basin is of great importance in hydrocarbon exploration and production. The Yinggehai-Song Hong Basin is one of the most important Cenozoic petroliferous basins in the South China Sea. To better understand the provenance characteristics of the Upper Miocene Huangliu Formation (Tortonian-Messinian) on the eastern margin of the basin and test the influence of uplift of the Tibetan Plateau in the South China Sea, 172 single zircons from two sandstone samples in the Lingtou gas field were dated by U–Pb chronometer, and 54 of these grains were spot analyzed for Hf isotopes. The results indicate that the upper member of the Huangliu Formation in this gas field shows two major peaks of U–Pb ages at ca. 250 Ma and ca. 432 Ma, along with four subordinate peaks at ca. 757 Ma, ca. 1926 Ma, ca. 2529 Ma and ca. 2775 Ma. The initial Hf isotope ratios [εHf (t)] of these zircons are negative to positive for each age group, suggesting that existing crustal materials were mixing with new mantle melts in some magmatic episodes. In contrast, the lower member of the Huangliu Formation show two major age peaks at ca. 98 Ma and 248 Ma, with a subordinate peak at ca. 1453 Ma. The εHf (t) values are concentrated between −11.6 and −3.4, revealing that they were derived from older crust. Comparing with the source characteristics of tectonic units surrounding the basin, the source of the upper member in the gas field was mainly from the southern Yangtze Block, whereas the lower member was derived from the Hainan Uplift. Together with the change of climate and sedimentation rate after 10 Ma on the northern margin of the South China Sea, we attribute the provenance change to the uplift of the Tibetan Plateau at the same time. Highlights: Detrital zircons from the eastern margin of the Yinggehai-Song Hong Basin were examined. The age spectra of the Upper and Lower members of Huangliu Formation show a striking difference. U–Pb ages and Hf isotopes indicate that the provenance changed in the Late Miocene. The provenance change may correspond to the uplift of the Tibetan Plateau.